If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + p) = x Reorder the terms: -9(p + x) = x (p * -9 + x * -9) = x (-9p + -9x) = x Solving -9p + -9x = x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9x' to each side of the equation. -9p + -9x + 9x = x + 9x Combine like terms: -9x + 9x = 0 -9p + 0 = x + 9x -9p = x + 9x Combine like terms: x + 9x = 10x -9p = 10x Divide each side by '-9'. p = -1.111111111x Simplifying p = -1.111111111x
| -13=17+x | | 3x-4=5(x+2) | | 4/5=n/20 | | (x+1)(x+3)=2(x+3) | | 2x+2/x-5=6 | | 5+(x-2/3)=(x+3/8) | | x2+2/x-5 | | 4x+9x=-39 | | b=7/4(j-49) | | 4x+2/2=17 | | 6x-2/5=8 | | 392+2x^2=1168 | | 3d=4(x-2) | | 18y+55x=2791 | | 1/55x+1/66x=1 | | -16-(-21)=x/6 | | 8x+20=3x+100 | | 1/2(4x+6)=1/3(9x-24) | | (5-y)-(6-y)=0 | | 9x-9/3=21 | | y=0.3x^2-4x+0.5 | | -5-2=13 | | 20x-10=14x+12 | | 4y+17=5x-4 | | -5x-2=1 | | 2x+42+1x-24=180 | | 4x+10=x+55 | | 14/y+6/2=2y-2 | | 15=-3+y | | 6(2x-4)=x-(4x-6) | | 2^-4+3/16 | | b+20=-7 |